A comparison of the efficacy and safety of combined aclidinium bromide and formoterol fumarate in the treatment of chronic obstructive pulmonary disease: A protocol for systematic review and meta-analysis. Issue 47 (20th November 2020) - Lu, Hong; Huang, Yi-Tong; Chen, He-Jiang; Chen, Pei-Feng
Abstract: Background: To systematically evaluate the efficacy and safety of combined aclidinium bromide and formoterol fumarate for chronic obstructive pulmonary disease (COPD). Methods: Electronic databases including PubMed, MEDLINE, EMBASE, Cochrane Library Central Register of Controlled Trials, WanFang, and China National Knowledge Infrastructure (CNKI) database were searched for studies on the use of combined aclidinium bromide and formoterol fumarate in the treatment of COPD. Two independent researchers performed literature screening, data extraction, and assessment of quality of studies. The strength of the association of the efficacy and safety of combined aclidinium bromide and formoterol fumarate in the treatment of COPD was evaluated according to the odds ratio (OR), mean differences (MDs), and 95% confidence interval (CI). Statistical analysis was carried out via using RevMan 5.3 software. Results: The results of the present study will be published in a peer-reviewed journal. Conclusion: The conclusion of the present study will provide evidence to judge whether combined aclidinium bromide and formoterol fumarate is an effective and safety intervention in the treatment of COPD. Systematic review registration number: INPLASY202070063.